NILAI-NILAI PENDIDIKAN BUDHI PAKERTI DALAM TOPENG PAJEGAN BALI - I Ketut Muada; I Wayan Sugama; I Made Indra Sanjaya (Widyadari, 2023)
The Pajegan Mask is also called the Guardian Mask, because it functions for religious ceremonies and is performed parallel to the gedog/weak wayang and is done right at the time the priests perform the ceremony. This mask determines Sidhaya or the success of a ceremony. The Sidhakarya Mask also functions as a roof where all deficiencies in religious ceremonies will be complemented by the Sidhakarya Mask. Based on this description, the researcher tries to examine this matter by giving the title "Budhi Pakerti Educational Values ​​in Balinese Pajegan Masks". As a formulation of the problem (1) What is the shape of Pajegan Masks in Bali? (2) What are the Buddhist Pakerti Educational Values ​​contained in Topeng Pajegan?. The theory used is aesthetic theory, metaphoric theory and simiotic theory, the method used is a structural approach. The type of study text is using a qualitative approach.